Bank Rate and Open Market Operations - Waugh, Robert W. (My University, 1940)
For nearly a century the financial world has been accustomed to experiencing wide and frequent fluctuations in the bank rate. However, since 1932, when the Bank of England's discount rate was pegged at 2 per cent. - at which figure it was maintained for seven years - low and stable rates have became accepted phenomena throughout the world. The old flexibility of the bank rate, which for generations in England was the traditional policy of the Bank, is gone, to be supplanted by a rigid and inflexible figure, drastically imposed. This thesis will attempt an investigation into the reasons for and results: of this change in policy.
Keywords: Political Economy